Antioxidant Activity Test And Permeability Test of Antioxidant Cream Preparation of 96% Ethanol Extract of Kaffir Lime Fruit Peel (Citrus hystrix) With The Addition of Enhancer - Meta Safitri; Syifa Afiatun Nisa; Firdanu Nupus; Mohammad Zaky; Nuriyatul Fathonah (Pharmacon: Jurnal Farmasi Indonesia, 2025)
This study aimed to determine the antioxidant activity, levels contained in kaffir lime peel extract, and penetration test on the antioxidant cream preparation of kaffir lime peel extract. This research method is experimental with descriptive analysis and SPSS. This extract was obtained by maceration using 96% ethanol and then standardizing the specific and non-specific extracts. The dosage form made is a cream with an extract concentration of 15% and modified enhancer variations F0 (without enhancer), F1 (10% propylene glycol), F2 (10% oleic acid), and F3 (5% propylene glycol and 5% oleate). The cream preparation was tested for physical evaluation of the preparation, % inhibition antioxidant activity using the DPPH technique and permeability test activity using Franz diffusion. The results showed that there were hesperidin levels of 25.34 mg/g, naringin 1.94 mg/g. Physical evaluation tests show that the cream fulfill all appropriate physical requirements, including homogeneity and organoleptic, pH, viscosity, spread ability, stickiness, cream type. The antioxidant activity of vitamins based on the inhibition percentage value is greater when compared to antioxidant cream, namely 41.604. The SPSS test uses One Way Anova, and the permeability test results of the largest cumulative amount and flux value were found in F2 with values ​​respectively 341.983 µg/cm2, 0.928 µg/cm2/minute. It can be concluded that the cream preparation made has antioxidant activity and permeability with the addition of 10% oleic acid enhancer which can influence penetration into the skin.